2011
DOI: 10.1038/npp.2011.66
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Antidepressant-Related Sexual Dysfunction: A Placebo-Controlled fMRI Study on Healthy Males Under Subchronic Paroxetine and Bupropion

Abstract: Sexual dysfunction is a common side effect of selective serotonin reuptake inhibitors (SSRIs) like paroxetine in the treatment of depression, imposing a considerable risk on medication adherence and hence therapeutic success. Bupropion, a norepinephrine and dopamine reuptake inhibitor, is recommended as an alternative treatment without adverse effects concerning sexual arousal and libido. We investigated the neural bases of paroxetine-related subjective sexual dysfunction when compared with bupropion and place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 58 publications
5
75
0
1
Order By: Relevance
“…Consistent with our finding of increased sexual arousal after methylphenidate, the DA precursor levodopa enhanced the activation of the nucleus accumbens when subliminal sexual stimuli were shown, whereas the DA D 2 -receptor antagonist haloperidol decreased activations (Oei et al, 2012). Accordingly, the DA and NE transporter inhibitor and antidepressant bupropion, which has less side effects on sexual arousal and libido than serotonergic antidepressants, increased activation of brain regions related to sexual functioning (Abler et al, 2011). Moreover, flibanserin, which enhances NE and DA while reducing 5-HT (Borsini et al, 2002), increased sexual desire in women with hypoactive sexual desire (Katz et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with our finding of increased sexual arousal after methylphenidate, the DA precursor levodopa enhanced the activation of the nucleus accumbens when subliminal sexual stimuli were shown, whereas the DA D 2 -receptor antagonist haloperidol decreased activations (Oei et al, 2012). Accordingly, the DA and NE transporter inhibitor and antidepressant bupropion, which has less side effects on sexual arousal and libido than serotonergic antidepressants, increased activation of brain regions related to sexual functioning (Abler et al, 2011). Moreover, flibanserin, which enhances NE and DA while reducing 5-HT (Borsini et al, 2002), increased sexual desire in women with hypoactive sexual desire (Katz et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…In a recent functional magnetic resonance imaging (fMRI) study in healthy subjects using primary rewards, we demonstrated decreased subcortical reward system activation under steady-state conditions of the SSRI paroxetine but not under the dopamine-norepinephrine reuptake inhibitor bupropion (Abler et al, 2011). No interaction effect of task and medication was observed in prefrontal brain areas.…”
Section: Introductionmentioning
confidence: 75%
“…Exclusion criteria were any psychiatric, neurological, and/or major medical diagnoses currently or in the past; any serious general medical condition; use of illegal drugs; excessive consumption of caffeine or alcohol; any regular systemic medication; and/or any other medication within the week before the study. Detailed sample characteristics and exclusion criteria were reported previously (Abler et al, 2011). Upon recruitment, subjects completed a German version (Reinecke et al, 2006) of the Massachusetts General Hospital Sexual Function Questionnaire (Labbate and Lare, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…It is not uncommon for substance misusers to experience difficulties with sexual performance owing to the effects of for example, opiates, methamphetamine and certain SSRI's. [16][17][18][19][20] Further, Arndt 21 stated that paraphilic infantilism often co-occurs with fetishism, masochism and/ or transvestism. Case 2 had expressed his sexuality via paraphilic transvestism whilst reverting to paraphilic infantilism following stimulant drug abuse.…”
Section: Case 2 Reportedmentioning
confidence: 99%